Home-Applied Dual-Light Photodynamic Therapy in the Treatment of Stable Chronic Periodontitis (HOPE-CP)-Three-Month Interim Results - Saila Pakarinen; Riitta K. T. Saarela; Hannamari Välimaa; Anna Maria Heikkinen; Esko Kankuri; Marja Noponen; Heikki Alapulli; Taina Tervahartiala; Ismo T. Räisänen; Timo Sorsa; Tommi Pätilä (MDPI AG, 2022)
A single-site, randomized clinical trial was designed to determine the efficacy of regular home use of Lumoral® dual-light antibacterial aPDT in periodontitis patients. For the study, 200 patients were randomized to receive non-surgical periodontal treatment (NSPT), including standardized hygiene instructions and electric toothbrush, scaling and root planing, or NSPT with adjunctive Lumoral® treatment. A complete clinical intraoral examination was conducted in the beginning, at three months, and at six months. This report presents the three-month results of the first 59 consecutive randomized subjects. At three months, bleeding on probing (BOP) was lower in the NSPT + Lumoral®-group than in the NSPT group (p = 0.045), and more patients in the NSPT + Lumoral®-group had their BOP below 10% (54% vs. 22%, respectively, p = 0.008). In addition, patients in the NSPT + Lumoral®-group improved their oral hygiene by visible-plaque-index (p = 0.0003), while the NSPT group showed no statistical improvement compared to the baseline. Both groups significantly reduced the number of deep periodontal pockets, but more patients with a reduction in their deep pocket number were found in the NSPT + Lumoral® group (92% vs. 63%, p = 0.02). Patients whose number of deep pockets was reduced by 50% or more were also more frequent in the NSPT + Lumoral®-group (71% vs. 33%, p = 0.01). Patients with initially less than ten deep pockets had fewer deep pockets at the three-month follow-up in the Lumoral® group (p = 0.01). In conclusion, adjunctive use of Lumoral® in NSPT results in improved treatment outcomes at three months post-therapy.